THE ROLE OF FAMILY SUPPORT IN ENHANCING PSYCHOLOGICAL WELL-BEING AMONG FINAL-YEAR EDUCATION STUDENTS - Fransiska Citra Pratiwi; Prias Hayu Purbaning Tyas (CV. TOTUS TUUS, 2025)
Final-year undergraduates face intense academic pressures, supervisory dynamics, and career uncertainty that can erode psychological well-being (PWB), while family support often serves as a primary resource in collectivist contexts. Objective: to assess the association between family support (emotional, informational, instrumental, appraisal) and Ryff-based PWB among final-year students. Quantitative correlational design at FKIP–Sanata Dharma University; sample n = 278 (Cohort 2021); 42-item family support scale (α = 0.969) and 39-item PWB scale (α = 0.918) using a 4-point Likert format; two-tailed Spearman’s ρ employed due to non-normality. Results: a strong positive association emerged between family support and PWB (ρ = 0.782; p < .001); family support levels were predominantly High/Very High (71.6%), as was PWB (70.5%), with only a small minority in lower categories. Higher perceived family support corresponds to better eudaimonic functioning (self-acceptance, autonomy, environmental mastery, positive relations, purpose in life, personal growth) during the thesis phase. Findings guide student services to screen for low family support and provide compensatory scaffolds (peer mentoring, writing/financial clinics) alongside autonomy-supportive family psychoeducation; at the policy level, they support enhancing advising capacity and structured family touchpoints at thesis milestones. Suggestions: future longitudinal, multivariate studies should test mediators (resilience, self-efficacy) and moderators (gender, SES, living arrangement), and differentiate support quality (autonomy support vs. control) in relation to specific PWB dimensions.